2014
DOI: 10.1038/nrneurol.2014.141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of neuromyelitis optica: state-of-the-art and emerging therapies

Abstract: Neuromyelitis optica (NMO) is an autoimmune disease of the CNS that is characterized by inflammatory demyelinating lesions in the spinal cord and optic nerve, potentially leading to paralysis and blindness. NMO can usually be distinguished from multiple sclerosis (MS) on the basis of seropositivity for IgG antibodies against the astrocytic water channel aquaporin-4 (AQP4). Differentiation from MS is crucial, because some MS treatments can exacerbate NMO. NMO pathogenesis involves AQP4-IgG antibody binding to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 237 publications
(231 citation statements)
references
References 180 publications
(200 reference statements)
4
221
0
6
Order By: Relevance
“…In 75% of NMOSD patients, autoreactive B cells produce antibodies against the aquaporin‐4 (AQP4) water channel (AQP4‐IgG) 2, 3. In the central nervous system (CNS), AQP4 is highly expressed on astrocyte end‐feet, and AQP4‐IgG has been shown to initiate an inflammatory cascade that ultimately leads to demyelination and neuronal injury 1, 4, 5. However, the location(s) of initial antigen presentation and affinity maturation, as well as the composition of migratory AQP4‐reactive B cells remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In 75% of NMOSD patients, autoreactive B cells produce antibodies against the aquaporin‐4 (AQP4) water channel (AQP4‐IgG) 2, 3. In the central nervous system (CNS), AQP4 is highly expressed on astrocyte end‐feet, and AQP4‐IgG has been shown to initiate an inflammatory cascade that ultimately leads to demyelination and neuronal injury 1, 4, 5. However, the location(s) of initial antigen presentation and affinity maturation, as well as the composition of migratory AQP4‐reactive B cells remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While 1 study reported that a monophasic disease course is more common in AQP4-IgG-negative patients [11], this was not found in another study [58]. It is unclear whether AQP4-IgG seronegative and seropositive NMOSD are driven by similar humoral immune mechanisms [29]. Therapeutic recommendations for AQP4-IgG-positive NMOSD cannot bona fide be transferred to seronegative patients, who should be treated on an individual basis, guided by severity and remission of the first attack and the clinical course [8].…”
Section: Prevention Of Nmosd Attacks General Considerationsmentioning
confidence: 93%
“…Several other complement inhibitors, for example monoclonal antibodies targeting C1, and compounds inhibiting C1 esterase activity, C3, or C3a and C5a receptors, were assessed in preclinical models or have been suggested for theoretical reasons [29].…”
Section: Complement Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations